2018
DOI: 10.1108/ijbm-05-2017-0104
|View full text |Cite
|
Sign up to set email alerts
|

Understanding undergraduates’ money management behaviour: a study beyond financial literacy

Abstract: Purpose The money management behavior of undergraduates determines their smooth transition into adulthood. Economic, social and psychological factors also affect undergraduates’ money management behavior. Therefore, the purpose of this paper is to investigate how undergraduates manage and respond to economic, social and psychological factors affecting their money management behavior, and to examine whether this response changes as they make progress in their degree. Design/methodology/approach Adopting a qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 71 publications
(136 reference statements)
0
23
0
3
Order By: Relevance
“…An adequate awareness of financial education is essential, not only for the established clients of the financial system, but also for persons currently experiencing financial exclusion and for young people. Hogarth et al (2002) showed that young people, in general, managed their financial resources poorly, due to the rapid evolution of financial products [43], deficiencies in their own abilities and the increasing use of technologies in this field [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…An adequate awareness of financial education is essential, not only for the established clients of the financial system, but also for persons currently experiencing financial exclusion and for young people. Hogarth et al (2002) showed that young people, in general, managed their financial resources poorly, due to the rapid evolution of financial products [43], deficiencies in their own abilities and the increasing use of technologies in this field [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…For quite a long time, studies have been attempting to get a better understanding of stock market participation and the parameters impacting individual's decisions whether or not participate in the stock market (Heaton and Lucas, 2000;Seasholes and Zhu, 2010;Korniotis and Kumar, 2011;Barber and Odean, 2013;Sivaramakrishnan et al, 2017;Bamforth et al, 2018;Ponchio et al, 2019). Previous studies have identified several factors that shape participation in the stock market, including demographics, education, social capital, income level, IQ level, investment knowledge, optimistic beliefs, financial literacy, peer effects, financial self-efficacy, stock market experiences, herding, heuristics, and cultural factors (Hong et al, 2004;Campbell, 2006;Brown et al, 2008;Georgarakos and Pasini, 2011;Grinblatt et al, 2011;Hurd et al, 2011;Malmendier and Nagel, 2011;Van Rooij et al, 2011;Bonaparte and Kumar, 2013;Calvet and Sodini, 2014;Kengatharan and Kengatharan, 2014;Li, 2014;Arrondel et al, 2015;Balloch et al, 2015;Gao, 2015;Gao et al, 2019;Liivamägi et al, 2019;Zou and Deng, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…It means that someone with a certain lifestyle will influence how they will manage their finances, including how they save their money. The factors that influence a person's saving behavior with qualitative research states that respondents with very large influence and have a luxurious lifestyle should tend to have a harder effort to manage finances [1] . On the other hand, respondents who choose friends wisely and manage their interactions only for close friends tend to be able to manage their finances well, including how to save their money.…”
Section: H1: Lifestyle Has a Significant Effect On Saving Behaviormentioning
confidence: 99%
“…The behavior of setting proportionally of income for a specific purpose in the present or the future. Bamford (2017) [1] Source: Data processed (2020)…”
Section: Financial Planning and Management 2 Financialmentioning
confidence: 99%